Amphetamine elevates nucleus accumbens dopamine via an action potential‐dependent mechanism that is modulated by endocannabinoids. (11th May 2016) - Covey, Dan P.; Bunner, Kendra D.; Schuweiler, Douglas R.; Cheer, Joseph F.; Garris, Paul A.
Abstract: The reinforcing effects of abused drugs are mediated by their ability to elevate nucleus accumbens dopamine. Amphetamine (AMPH) was historically thought to increase dopamine by an action potential‐independent, non‐exocytotic type of release called efflux, involving reversal of dopamine transporter function and driven by vesicular dopamine depletion. Growing evidence suggests that AMPH also acts by an action potential‐dependent mechanism. Indeed, fast‐scan cyclic voltammetry demonstrates that AMPH activates dopamine transients, reward‐related phasic signals generated by burst firing of dopamine neurons and dependent on intact vesicular dopamine. Not established for AMPH but indicating a shared mechanism, endocannabinoids facilitate this activation of dopamine transients by broad classes of abused drugs. Here, using fast‐scan cyclic voltammetry coupled to pharmacological manipulations in awake rats, we investigated the action potential and endocannabinoid dependence of AMPH‐induced elevations in nucleus accumbens dopamine. AMPH increased the frequency, amplitude and duration of transients, which were observed riding on top of slower dopamine increases. Surprisingly, silencing dopamine neuron firing abolished all AMPH‐induced dopamine elevations, identifying an action potential‐dependent origin. Blocking cannabinoid type 1 receptors prevented AMPH from increasing transient frequency, similar to reported effects on other abused drugs, but not from increasing transient duration and inhibiting dopamine uptake. Thus, AMPH elevates nucleus accumbens dopamine by eliciting transients via cannabinoid type 1 receptors and promoting the summation of temporally coincident transients, made more numerous, larger and wider by AMPH. Collectively, these findings are inconsistent with AMPH eliciting action potential‐independent dopamine efflux and vesicular dopamine depletion, and support endocannabinoids facilitating phasic dopamine signalling as a common action in drug reinforcement. Abstract : We found that amphetamine elevates nucleus accumbens dopamine in awake rats by eliciting phasic release events via a mechanism that requires dopamine cell firing and is modulated by endocannabinoids. These findings contradict amphetamine's canonical mechanism but are consistent with a common action in drug reinforcement.